A minimal critical set of a class of youden squares - Fitina, Lakoa; Russell, Kenneth G.; Seberry, Jennifer (Utilitas Mathematica, 2006)
We consider the Youden square formed by deleting one row of a v × v back-circulant Latin square and establish a critical set that contains a number of elements which is equal to v2/4 (v even) or (v2 - 1)/4 (v odd). We show that this critical set is minimal, for v even.